Interferon Kappa Is Up-Regulated in Psoriasis and It Up-Regulates Psoriasis-Associated Cytokines in vivo - Li Y; Song Y; Zhu L; Wang X; Yang B; Lu P; Chen Q; Bin L; Deng L (Dove Medical Press, 2019)
Yuanyuan Li,1,* Yueqi Song,1,* Leqing Zhu,1,* Xiao Wang,1 Bin Yang,2 Ping Lu,2 Quan Chen,3 Lianghua Bin,4 Liehua Deng5 1Biomedical Translational Research Institute, The First Affiliated Hospital, Jinan University, Guangzhou, Guangdong Province, People’s Republic of China; 2Department of Dermatology, Dermatology Hospital of Southern Medical University, Guangzhou, Guangdong Province, People’s Republic of China; 3Division of Research Informatics Services, Department of Medicine, National Jewish Health, Denver, CO, USA; 4Department of Pediatrics, National Jewish Health, Denver, CO, USA; 5Department of Dermatology, The First Affiliated Hospital, Jinan University, Guangzhou, Guangdong Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lianghua BinDepartment of Pediatrics, National Jewish Health, 1400 Jackson Street, Denver, CO 80206, USATel +1-303-270-2055Email binl@njhealth.orgLiehua DengDepartment of Dermatology, The First Affiliated Hospital, Jinan University, West Huangpu Dadao, No 605, Tianhe Qu, Guangzhou, Guangdong Province, People’s Republic of ChinaTel +86-137-25356728Email liehuadeng@126.comPurpose: There is increased type I interferon signature in psoriasis patients. Interferon-kappa (IFN-κ) is a member of type I interferon family that is constitutively expressed by keratinocytes. In this study, we investigate whether IFN-κ is involved in psoriasis etiology.Patients and methods: Twenty healthy individuals, 20 psoriasis vulgaris patients and 10 atopic dermatitis (AD) were included for this study. Immunohistochemistry staining, normal human epidermal keratinocytes (NHEK) culture, Ca2Cl-induced differentiation, quantitative reverse transcription (qRT-PCR), ELISA and murine experiments were performed.Results: We found IFN-κ protein expression was extremely low in the epidermis of normal skin, but it was significantly increased in the suprabasal layers of epidermal keratinocytes in psoriatic skin lesions. However, its expression in the skin lesions of AD was similar to normal skin. Additionally, IFN-κ protein was detected in sera from psoriasis patients, but not in sera from normal subjects and AD. We further investigated the regulation of IFNk gene expression in NHEK. We found that IFNk was significantly induced by types of nucleic acid pathogen recognition receptor (PRR) agonists in NHEK. While its expression was significantly induced by itself and IFN-γ, it was inhibited by type 2 immunity cytokines IL4 and IL13; other inflammatory cytokines including IL1 super-family members and IL17A did not alter its expression. Addition of recombinant IFN-κ did not affect keratinocytes differentiation. Using the murine experimental model, we demonstrated that subcutaneous administration of recombinant IFN-κ did not increase skin thickness, but significantly increased the transcription of TNFA and IL17A in mice skin.Conclusion: Increased IFN-κ in psoriasis may be caused by injured cells-released nucleic acids, increased IFN-γ and self-activation. Its enhancement may contribute to the etiology of the disease by enhancing TNFA and IL17A gene expression.Keywords: IFN-κ, psoriasis, TNFA, IL17A, atopic dermatitis